Difficulty producing high-pitched sounds in singing: correlations with laryngostroboscopy and electromyographic findings - Korn,Gustavo Polacow (2020)
Abstract Introduction: Difficulties or limitations in producing high-pitched sounds while singing may be due to the vocal technique used or organic factor. The observation of such difficulty or limitation by singing teachers is one of the main reasons affected individuals are referred to otolaryngologists. Objective: To evaluate the laryngostroboscopic and electromyographic changes in the cricothyroid muscles of singers with difficulties or limitations producing high-pitched sounds. Methods: This is a cross-sectional study. Ten singers with difficulty producing high-pitched sounds underwent voice, laryngostroboscopic, and electromyographic evaluations. Results: None of the evaluated singers presented signs of impairment of the superior laryngeal nerve on laryngostroboscopy. The electromyographic findings for the cricothyroid muscle were normal for all singers. Six singers presented vocal fold lesions, seven had signs suggestive of laryngopharyngeal reflux, and two presented vascular changes. Conclusion: No signs suggestive of superior laryngeal nerve paresis or paralysis were observed on laryngostroboscopy and electromyography of the cricothyroid muscle in singers with difficulties or limitations producing high-pitched sounds. The presence of vocal fold lesions should be investigated in this population.